Preparation and properties of zirconium tungstate with anomalous thermal characteristics - Elena Dedova; Vladimir Shadrin; Alexander Gubanov; Sergey Kulkov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The main aim of the study: The actuality of the discussed issue is caused by the lack of systematic studies of structural phase transformations of zirconium tungstate at temperature increase. The methods used in the study:High temperature in situ X-ray analysis, refinement of the structure by the Rietveld method using TOPAS v.4.2 (Bruker) software, thermogravimetric differential scanning calorimetry. The results: The morphology of the material was represented as rod-shaped particles having a block structure. The ZrW2O8 synthesized was kinetically stable from 25 to 540 °C. Temperature increase has initiated structural change which resulted decomposition of ZrW2O8 into ZrO2 and WO3. The ZrW2O8 synthesized demonstrated a negative thermal expansion behavior from 25 to 750 °C.